Functions of the 'theatrical' plot in M.A. Bulgakov's fantastic vaudeville 'Ivan Vasil'evich' - M.A. Shelenok (Ученые записки Казанского университета: Серия Гуманитарные науки)
This paper conceptualizes an important literary problem: the transformation of the vaudeville genre in the Russian drama of 1920–1930. The relevance and novelty of the research are due to identification of the role of the “theater” plot, which is typical of the classic vaudeville, in the structure of the play “Ivan Vasilievich” by M.A. Bulgakov (this aspect has not been taken into consideration in the works of the Bulgakov scholars). The study aims is to reveal the specifics of the “theatrical” plot and its functions in M.A. Bulgakov's work. Based on the results of the study, the following conclusions have been made. The traditional plot about the actress is subordinate in the storyline of the play “Ivan Vasil'evich” and develops as a parody. The ironically interpreted plot twists of “theatrical” vaudeville and love collisions make fantastic action of the play more typical if common life and psychologically deeper, and the image of the time machine's inventor becomes less schematic. M.A. Bulgakov creates a new version of the genre, in which he mocks the classic vaudeville tricks, plot moves, and characters. The behavior of characters is theatrized, but in different ways. Thus, there is the author's irony towards the characters that are carried away with their own playing (the actress Zinaida and the director Yakin), who are opposed to George Miloslavsky, a rogue, whose acting looks more natural, elegant, and gives an ironic assessment of the Soviet reality of the 1930s. The fantastic beginning allows the author to “play” not only with comic situations while travelling in time, but also with the dramatic similarity between the time periods, thereby introducing some serious moments and a tragic subtext into the vaudeville. Thus, M.A. Bulgakov brings the Soviet vaudeville to a new level with the help of not only fiction, grotesque, and sharp satirical wit, but also play modification of the “theatrical” plot traditional for the vaudeville of the 19th century.